Characterization of the activity and the mechanism of action of a new toluquinol derivative with improved potential as an antiangiogenic drug. - Torres-Vargas, José Antonio; Cheng-Sánchez, Iván; Martínez-Póveda, Beatriz Amparo; Medina-Torres, Miguel Ángel; Sarabia-García, Francisco Ramón; García-Caballero, Melissa; Rodríguez-Quesada, Ana María (Elsevier, 2022)
The inhibition of sustained angiogenesis is an attractive approach for the treatment of cancer, blindness and other angiogenesis-dependent diseases. Encouraged by our previous finding that toluquinol, a methyl hydroquinone isolated from a marine fungus, exhibited an interesting antiangiogenic activity, we further explored structural modifications of this natural compound in order to develop improved drug candidates. Our results indicate that although the methyl group plays a relevant role in the cytotoxic activity of toluquinol, some derivatives in which this methyl was replaced by another substituent, could keep the antiangiogenic activity, whereas exhibiting a lower cytotoxicity in vitro. This is the case of (E)- 2-(3-methoxyprop-1-en-1-yl) benzene-1,4-diol, which exhibits a decreased toxicity, whereas maintaining or even improving the antiangiogenic activity of toluquinol, as demonstrated by a number of in vitro (endothelial cells proliferation, migration and tube formation) and in vivo (chick embryo chrorioallantoic membrane vascularization and murine corneal neovascularization) experimental approaches. Our results point to a mechanism of action that could be related to an induction of apoptosis, as well as to an increase in the reactive oxygen species levels, a reduction of the redox capacity and the inhibition of the VEGFR2, Akt and ERK phosphorylation in VEGF-activated endothelial cells. The biological activity of this new angiogenesis inhibitor, along with its lower undesired toxicity, suggests that it is a promising drug candidate with improved potential for the treatment of angiogenesis-related diseases.
Keywords: Antiangiogénicos; Neovascularización; (E)− 2-(3-methoxyprop-1-en-1-yl) benzene-1; Angiogenesis; Antiangiogenic drug; Toluhydroquinone